2020
DOI: 10.29244/jli.v12i2.32533
|View full text |Cite
|
Sign up to set email alerts
|

Toleransi Tanaman Lanskap Terhadap Pencemaran Udara di Kota Sidoarjo

Abstract: Landscape plants is one of horticultural plants, wich has a few functions, such as for esthetics plant, giving shade on the road, hedges and absorbing air pollution. Judging from its existence, landscape plants are often facing problem, such as clash with air pollution, as a result of the process of photosynthesis on the plants are disrupted. This research is conducted in two locations in the city of Sidoarjo, at the Alun-alun Sidoarjo area as the control location (L0) and Aloha area as the polluted location (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Tanaman memiliki fungsi penting yaitu dapat menyerap polutan. 13 Untuk pemulung dapat menggunakan Alat Pelindung Diri (APD) seperti masker untuk bahwa dengan menggunakan masker, pemulung tersebut akan terhindar dari kemungkinan terjadinya gangguan pernapasan. Masker yang dapat digunakan untuk mengurangi paparan H2S yaitu masker kain (mechanical respiratory) atau masker bertabung (carvadge respiratory).…”
Section: Manajemen Risikounclassified
“…Tanaman memiliki fungsi penting yaitu dapat menyerap polutan. 13 Untuk pemulung dapat menggunakan Alat Pelindung Diri (APD) seperti masker untuk bahwa dengan menggunakan masker, pemulung tersebut akan terhindar dari kemungkinan terjadinya gangguan pernapasan. Masker yang dapat digunakan untuk mengurangi paparan H2S yaitu masker kain (mechanical respiratory) atau masker bertabung (carvadge respiratory).…”
Section: Manajemen Risikounclassified
“…Meanwhile, the results of an APTI study in Sidoarjo revealed that polluted locations had higher APTI Pterocarpus indicus and Syzygium oleana values than control locations. Because plants grow in areas near highways, it is suspected that they can defend against air pollution, which is supported by physiological parameters such as pH, ascorbic acid, water content, or high chlorophyll [14].…”
Section: Introductionmentioning
confidence: 99%